Las Cántigas de alén de José Ángel Valente: tradición y ruptura de la poesía gallega - Martínez-falero, Luis (Madrygal. Revista de Estudios Gallegos, 2010)
José Ángel Valente has only published a book in Galician, Cántigas de Alén. In this article we propose a study of Comparative literature between Valente’s work in Galician and his production in Castilian, and also the relationship with other authors regarding literary imaginary.
Keywords: Poetry; Imaginary; Comparative literature